Integration of Naqli and Aqli in Microbiology Teaching: Sharing the Experience - Mohamed, NA; Shahida, W; Isahak, I; Alias, N; Anuar Sani; Zarini Ismail (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/SCOPUS